SPATIOTEMPORAL VARIATION OF PARTICULATE MATTER (PM) 2.5 CONCENTRATION IN THE INDONESIAN MARITIME CONTINENT - Napitupulu, Gandhi; Zulfikar, Rafid; Yulianti, Kadek Krisna; Sinuraya, Deta Ewila; Waryatno, Nur Faris Prih; Fekranie, Naffisa Adyan (Malaysian Journal of Tropical Geography (MJTG), 2024)
Indonesia is recognized as the country with the highest level of Particulate Matter (PM) 2.5 pollution in Southeast Asia. This study aims to investigate the spatial and temporal variations of PM2.5 concentrations in the Indonesian maritime continental region (IMC) over a span of 38 years (1980-2018), based on seasonal and El Niño-Southern Oscillation (ENSO) phenomena. The data used are surface PM2.5, rainfall, wind components at 850 hPa pressure, and fire hotspot points in the IMC region. The results showed higher PM2.5 anomalies in summer (JJA) compared to winter (DJF). There is a positive PM2.5 anomaly during the JJA period and a negative anomaly during the DJF period in the IMC region, which is caused by particle deposition by rain. Seasonal wind patterns carry pollutants from urban areas and hotspots towards the countryside, significantly increasing PM2.5 concentrations in rural areas. Riau and South Sumatra provinces show the highest hotspot density on Sumatra Island, Central Kalimantan and West Kalimantan provinces show the highest hotspot density on Kalimantan Island, and southern Papua has the highest hotspot density on Papua Island. The peak number and density of hotspots in Sumatra, Kalimantan, and Papua occurred in September. The rainfall patterns in IMC are closely linked to ENSO years. During El Niño years, rainfall decreases, and the atmosphere tends to become drier, leading to an increase in hotspots. These hotspots contribute to elevating the concentrations of PM2.5, as observed in 1997/1998 and 2015/2016 when the region experienced its highest hotspot density and a corresponding rise in PM2.5 levels. This association underscores the complex interplay between climatic phenomena, atmospheric conditions, and air quality dynamics in the Indonesian context.